Cardiac shock care center — the next stage in the treatment of cardiogenic shock - S. A. Boytsov; R. S. Akchurin; D. V. Pevzner; R. M. Shakhnovich; M. Ya. Ruda (Российский кардиологический журнал)
The key step in achieving a significant reduction  in mortality in patients  with myocardial infarction (MI) was the organization of a wide network of specialized PCI-centers that provide care for patients with acute coronary syndrome (ACS) on the 24/7 mode  in accordance   to clear protocols. However,  currently in-hospital  mortality  of MI patients,  complicated  by cardiogenic  shock (CS), remains extremely high and averages 50 %. The formation of a system of highly specialized centers seems to be the most promising opportunity to improve the prognosis of patients  with CS. The article discusses  the world scientific and clinical experience in organizing cardiac shock care centers, the features of their internal structure, as well as the administrative and logistical aspects  of entire system operation.